Prediction of chloride profile at crack location in reinforced concrete under flexural loading. - Vu, Hoang Quoc
The chloride penetration into concrete is one of the most popular topics and very exciting in the field of concrete durability. The chloride ion acts as a main factor in causing the corrosion of the reinforcement in concrete structure. Moreover, chloride tranport mechanisms in concrete are very complicated. Specifically, the cracks were recognized as one of the primary reasons causing an increase in the corrosion rate of reinforcements due to chloride attack. The aim of this research is to propose models for predicting the chloride profile at crack locations of reinforced concrete. In the present paper, the tapered crack (V-shaped crack) was introduced as a natural crack due to flexural loads. In addition to the crack width, the crack depth also played as a factor influencing the chloride penetration depth and chloride profile. Finally, the validity of the proposed model was verified by comparing with experimental results under the influence of crack characteristics. The research results showed that the predicted results fitted well with experimental ones when the immersion periods were larger than 4 weeks.
Keywords: Chloride Penetration; Chloride Profile; Cracked concrete; Crack depth; Crack Width